Overlapping Receptor-Based Pathogenic Cascades in Degenerative Disease: Implications Ranging from Tumor Targeting to Aging and Dementia Therapeutics - Joseph S. D’Arrigo (International Journal of Translational Medicine, 2024)
Previous research has already shown that apolipoprotein (apo)A-I is adsorbed from the bloodstream onto the surface of certain colloidal lipid particles after the intravenous injection of such colloidal nanocarriers. As a result, various blood–brain barrier (BBB) scavenger receptors are targeted by these (apoA-I-coated) colloidal nanocarriers. This targeted molecular interaction is mediated/facilitated by the adsorbed apoA-I, which is then followed by receptor-mediated endocytosis and subsequent transcytosis of the nanocarrier particles across the BBB. A multifunctional combination therapy is obtained by adding the appropriate drug(s) to these biomimetic (lipid cubic phase) nanocarriers. This therapeutic targets specific cell-surface scavenger receptors, primarily class B type I (SR-BI), and crosses the blood–brain barrier. The lipid contents of artificial biomimetic (nanoemulsion) nanocarrier particles and of naturally occurring high-density lipoproteins (HDL) have been shown to be similar, which enables these nanocarrier particles to partially imitate or simulate the known heterogeneity (i.e., subpopulations or subspecies) of HDL particles. Hence, colloidal drug nanocarriers have the potential to be used in the biomedical treatment of complicated medical conditions including dementia, as well as certain elements of aging. Widespread inflammation and oxidative stress—two processes that include several pathophysiological cascades—are brought on by dementia risk factors. More recent studies suggest that proinflammatory cytokines may be released in response to a prolonged inflammatory stimulus in the gut, for example through serum amyloid A (SAA). Therefore, pharmacologically targeting a major SAA receptor implicated in the SAA-mediated cell signaling processes that cause aging and/or cognitive decline, and ultimately Alzheimer’s disease or (late-onset) dementia, could be an effective preventive and therapeutic approach.